Sistem Informasi Geografi dan Penginderaan Jauh dalam Pemetaan Zona Longsor Lahan di Kawasan Terbangun - Mohammad Amin Lasaiba (Universitas Indraprasta PGRI Jakarta, 2023)
Landslide is a natural hazard that is quite widespread throughout the world and has caused casualties and ruined people's economic livelihoods. This study uses qualitative and quantitative methods combined with a spatial approach to analyze primary and secondary data from satellite imagery, observation, and related agencies. Data processing is conducted using Global Mapper 20, Arcgis 10.8.1 and Ermapper 8.1 softwares. The results obtained from this study show that the vulnerability to landslides is relatively high, with a large area around 51.63%. This area is spread over hilly areas. For built land, its level of vulnerability to landslide in both the high and very high categories, namely in zones Z-4 and Z-5, is caused by slopes of 25 to > 40%, with rock types with a high degree of weathering and with built-up land cover. The use of remote sensing and geographic information system in assessing landslide in the research area can be used as a guide for the proper use of land to avoid disasters that may occur.